PEMODELAN STRUKTUR DENGAN METODE BIM MENGGUNAKAN SOFTWARE AUTODESK REVIT - Hariyanto, Hariyanto; Dwi Kurniawan, Muchlas Adi (Universitas PGRI Semarang, 2024)
The need for technology in the world of construction is very important, good use of technology can facilitate the completion of the construction process. One of the developments in digital technology that has had a significant impact in accelerating infrastructure development is Building Information Modeling (BIM). The BIM software used is Autodesk Revit. This research aims to model the structure of the Hibatullah Kasiman Islamic boarding school dormitory building using Autodesk Revit software to calculate work volume and cost estimates, then carry out comparative analysis with conventional methods. Structural modeling includes concrete work and reinforcement in foundations, sloofs, columns and beams. The research results showed that the volume of concrete work using Autodesk Revit software was 861.84 mÂ³, and the estimated cost of concrete work was IDR 1,159,002,226.60, while the volume of reinforcement was 123089.27 kg, and the estimated cost of reinforcement was IDR 2,144,978,024.97. The difference between the volume and estimated cost of concrete work using Autodesk Revit and conventional software was found to be 4.48%, while the difference between the volume and estimated cost of reinforcement was 10.69%. Calculations using Autodesk Revit software are fewer and cheaper than conventional ones, conventional volumes calculated are still rough and less detailed, there are many discrepancies in values with those in the drawings, and more estimates are made to anticipate material shortages at the time. work in the field.